Sociālpedagoģiskā darbība 5.-7. klašu skolēnu iecietības veicināšanā klasē - Lejiņa, Linda (Latvijas Universitāte, 2022)
Par Lindas Lejiņas diplomdarba tēmu tika izvēlēta “Sociālpedagoģiskā darbība 5.-7. klašu skolēnu iecietības veicināšanā klasē”. Pētījuma mērķis ir raksturot iecietību, skolēnu atšķirības, neiecietības veidus un izpausmes 5.-7. klasēs, kā arī izstrādāt un aprobēt sociālpedagoģisko programmu skolēnu iecietības veicināšanā. Teorētiskajā daļā ir analizēta iecietības būtība, aprakstītas skolēnu atšķirības, neiecietības veidi un to izpausmes. Praktiskā daļa sastāv no pētījuma par iecietību 5.-7. klasēs, kā arī tajā iekļauta sociālpedagoģiskās darbības programma un tās aprobācija 5.-7. klašu skolēnu iecietības veicināšanā klasē. Sociālpedagoģiskā programma tika izveidota, pamatojoties uz veikto pētījumu Rīgas “X” pamatskolā. Atslēgvārdi: iecietība, neiecietība, skolēnu atšķirības, sociālpedagoģiskā darbība.

The theme of the diploma paper of Linda Lejina is “Social pedagogical activity in grades 5-7 to increase tolerance of students in the class.” The aim of this research is to describe tolerance, students’ individual differences, types and manifestations of intolerance as well as to develop and approbate a socio-pedagogical programme promoting tolerance among students in grades 5-7. The theoretical part analyzes the nature of tolerance and describes individual differences of students. It also deals with various types and manifestations of intolerance. The practical part consists of a research on tolerance in grades 5-7. It includes a socio-pedagogical activity programme created in order to promote tolerance and its approbation results in grades 5-7. The socio-pedagogical programme was developed on the basis of the research conducted in Riga "X" elementary school. Key words: intolerance, socio-pedagogical activity, students’ differences, tolerance.
Social pedagogical activity in grades 5-7 to increase tolerance of students in the class
Keywords: Pedagoģija; iecietība; neiecietība; skolēnu atšķirības; sociālpedagoģiskā darbība